Swedish Experiences From 60 Years of Screening and Breeding Programs for Hip Dysplasia—Research, Success, and Challenges - Hedhammar, Åke (Frontiers in Veterinary Science, 2020)
A screening program for Hip Dysplasia (HD) was introduced in Sweden during the 50th for German shepherds – soon for more breeds and now any breed. In Sweden 70 % of all dogs are registered by the Swedish Kennel Club and in relevant breeds almost all breeding stock and 30- 50% of all dogs are screened for HD. By an extensive database on all dogs registered since 1976 and mandatory identification by microchip all results can be linked to well-defined dogs. An implementation of structured screening and breeding programs resulted in markedly decreased prevalence of HD already during the 1980s. The programs are based on open registries, on positive as well as negative result for identified individuals linked to their ancestral background. The successful decrease in of moderate and severe HD is illustrated for seven common breeds. However, there is also the challenge of further decrease when already almost all breeding is performed with unaffected breeding stock. To handle that and an increased relative prevalence of less severe grades of HD (grade C) calls for breed specific breeding strategies, taking into account the prevalence and clinical significance in each breed. Further decrease might rather be achieved by usage of breeding indexes and genomic selection than more extensive and costly screening procedures. For the public perception of HD, the value of a clear distinction between grades D-E as a good predictor of the clinical entity versus grade C as a tool to refine the selection criteria for breeding stock, is indicated.